Growth Characteristics of a Desmodesmus Species from the San Antonio Springs and Its Short-Term Impact on Soil Microbial Dynamics - Lauren K. Bomer; Betsy D. Leverett (Life)
A new Desmodesmus species was isolated from the largest of the San Antonio Springs, the Blue Hole, in San Antonio, Texas, and characterized for its potential applications in sustainable agriculture. The xenic isolate (XB) was established by enrichment and subcultured to produce the axenic isolate (AxB), which was identified based on morphological features and DNA profiling, confirming its close phylogenetic relationship with Desmodesmus spp. Growth characteristics, biomass composition, and pigment profiles were assessed for both the xenic and axenic isolates along with their growth in saline conditions and a range of seasonal Texas temperatures. Both Desmodesmus XB and Desmodesmus AxB exhibited optimal growth at 25 °C as well as robust growth at 37 °C and in weakly saline media (5 g/kg NaCl). Biomass analysis revealed levels of carbohydrates, proteins, lipids, chlorophylls, and carotenoids comparable to other desmids and pigment profiles supported the Desmodesmus classification. Soil studies demonstrated the persistence of Desmodesmus XB and influence on microbial activity, indicating the potential of this isolate for agricultural applications such as soil remediation.